2019
DOI: 10.1177/1043463119841033
|View full text |Cite
|
Sign up to set email alerts
|

Ideology and the rationality of non-voting

Abstract: What is the theoretical impact of the erosion of partisan ties on electoral abstention? This question comes from Downs–North’s theory of political ideology, which is a tool to reduce the cost of understanding the political debates. Then, when the left–right political divide becomes less visible, the costs of understanding political debates rise and electoral abstention occurs. This interpretation of abstention has three implications: first, it shows that among the multiple reasons responsible for the ‘democrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…At the same time, however, the Front National adopted a more hostile stance towards Islam (Mayer, 2013(Mayer, , 2015. This approach has arguably assisted the competitiveness of the party in French elections as social values appear to take on more prominence than the traditional economic left/right divide in politics (Facchini and Jaeck, 2019). In the Netherlands, openly-gay Pim Fortuyn led a populist movement calling for an end to Muslim immigration before his assassination in 2002 and the political space he occupied has since been filled by Geert Wilders' Party for Freedom, which similarly combines tolerance towards women's rights, LGBT people and Jews with hostility towards Islam (Akkerman, 2005;Vossen, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, however, the Front National adopted a more hostile stance towards Islam (Mayer, 2013(Mayer, , 2015. This approach has arguably assisted the competitiveness of the party in French elections as social values appear to take on more prominence than the traditional economic left/right divide in politics (Facchini and Jaeck, 2019). In the Netherlands, openly-gay Pim Fortuyn led a populist movement calling for an end to Muslim immigration before his assassination in 2002 and the political space he occupied has since been filled by Geert Wilders' Party for Freedom, which similarly combines tolerance towards women's rights, LGBT people and Jews with hostility towards Islam (Akkerman, 2005;Vossen, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ideological indistinctiveness would fuel disinterest in politics, and ultimately, electoral abstention (Facchini and Jaeck, 2019). However, in such cognitive contexts whereby the costs of gathering and processing political information become prohibitive, behavioral economics teaches us that in order to reduce these costs, individuals rely on the heuristic of availability to form their opinions (Kuran and Sunstein, 1999;Tversky and Kahneman, 1974).…”
Section: The Voting Costsmentioning
confidence: 99%
“…The PS moved 23.1 to the right between 1978 and 2002 and the RPR/UMP moved 28.0 points to the left. The primary effect of ideological indistinctiveness is electoral abstention since voters can no longer make the distinction between traditional left-wing and right-wing parties (Facchini and Jaeck, 2019). The secondary effect is twofold.…”
Section: Ideological Indistinctiveness: a Catalyst For Populismmentioning
confidence: 99%
See 1 more Smart Citation
“…Political parties and voters' election behavior and results attract considerable research attention (e.g. in this journal, Facchini and Jaeck, 2019;Pensiero, 2020). In US history, there are a lot of unexpected election outcomes.…”
Section: Introductionmentioning
confidence: 99%